ANALISIS PENGARUH LITERASI DIGITAL TERHADAP NILAI-NILAI ETIKA BERDIGITAL PADA MAHASISWA PENDIDIKAN AGAMA ISLAM DI IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG - Sari, Diah Arum Kartika; Sari, Nopita (Journal of Research and Thought on Islamic Education (JRTIE), 2023)
This research was conducted to determine whether there is an influence of digital literacy on the digital ethical values of students in the Islamic Religious Education Study Program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. In this research, researchers used a quantitative approach with the Ex Post Facto method. The location of this research was IAIN Syaikh Abdurrahman Siddik Bangka Belitung. The population of this study was 260 students in the Islamic Religious Education Study Program in 2023, then a sample of 155 students was obtained. The data collection technique used was an online questionnaire/questionnaire via Google Form. The data analysis used is the analysis prerequisite test, namely the normality test and homogeneity test, then hypothesis testing using the regression equation and t test. The results of this research are that there is a significant influence between digital literacy and the digital ethical values of students of the Islamic Religious Education Study Program at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. Based on the t value, the t-count value = 1.943 and the t-table value = 1.65474 (1.943 1.65474). ) based on these values can be categorized as significant, so that there is an influence of digital literacy on digital ethical values.